PROFIL PEMECAHAN MASALAH MATEMATIKA TERBUKA SISWA BERKEMAMPUAN MATEMATIKA TINGGI DI SMP KELAS VIII SMP MUHAMMADIYAH 17 PLUS SURABAYA - Deddiliawan Ismail, Agung (Universitas Ahmad Dahlan, 2011)
In daily life, people are always having problems. The problem has many solutions or a solution only to solve it. In learning mathematics, there is open-ended problem that is also a problem that has many ways of solving. Polya (1973) argues that there are four steps in solving the problem. They are: (1) understand the problem (understanding the problem), (2) make a plan (devising a plan), (3) implementation (carrying out the plan), (4) re-examine (looking back). By seeing the results of several studies suggest that the ability level of students affect the process of solving math problems. Based on this background then, the problem that also the focus of this research was